Agronomic characteristics of Prata type banana plants under different irrigation systems - Marques, Pedro Ricardo Rocha; Donato, Sérgio Luiz Rodrigues; Pereira, Marlon Cristian Toledo; Coelho, Eugênio Ferreira; Arantes, Alessandro de Magalhães (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate the agronomic characteristics of Prata banana plants during three production cycles, under different irrigation systems, in semi-arid conditions. A randomized block design was adopted with six treatments, in a 3x2 factorial arrangement: three irrigation systems – conventional sprinkler, microsprinkler and drip – and two genotypes – ’Prata-Anã’ and its hybrid PA42-44. Four replicates in plots with six useful plants were used. Plant height, pseudostem perimeter, number of alive leaves, length and width of the third leaf, total leaf area, and leaf area index were evaluated at flowering. Weight of bunch and hands, mean weight of hands, weight of the three first hands, number of hands and fruits per bunches, and weight, length and diameter of fruits and number of alive leaves were evaluated during the harvest season. The drip irrigation system provides smaller vigor to banana Prata, in comparison to conventional and to micro sprinkler systems, as can be seen by the size and perimeter of the pseudostem. The cultivar Prata-Anã shows a larger number of fruit and hands per brunch, while its hybrid PA42-44 shows larger weight, length and fruit diameter.